Gene Expression Profile of Pulmonary Tissues in Different Phases of Lung Ischemia-reperfusion Injury in Rats - 李劲松 聂君 陈刚 龚勇泉 江科 杨光海 刘磊 王建军 (Journal of Huazhong University of Science and Technology. Medical sciences, 2007)
In order to provide us new clues to induce some endogenous protective molecular mechanisms, the changes in gene expression profile induced by ischemia-reperfusion in pulmonary tissues of rats were investigated and the dynamic mechanism of pulmonary ischemia-reperfusion injury was elucidated. Thirty male Wistar rats were randomly divided into 6 groups： 5 ischemia-reperfusion （I/R） groups （I/R 0-h, I/R 1-h, I/R 3-h, I/R 6-h, I/R 24-h） and control group （n=5 in each）. An in situ ischemia-reperfusion lung injury rat model was established by occluded hilus of lung. The RatRef-12 Expression Beadchip （22 226 gene probes per array） was used to analyze the pattern of gene expression in all groups. The results showed that 648, 340, 711, 1279 and 641 genes were differentially expressed in I/R 0-, 1-, 3-, 6- and 24-h groups respectively. The differentially expressed genes were classified as following 7 functional categories： cytokine, adhesion molecule, growth factor and apoptosis-related factor, oxidation and antioxidation molecule, metabolic enzyme, ion channel and aquaporin, signal transduction molecule. It was suggested that gene chip technology was an effective and quick method for screening differentially expressed genes. Many differentially expressed genes with different functions interacted each other to result in pulmonary ischemia-reperfusion injury.